KEKUASAAN PARTAI SIMPLE MAJORITY DALAM FORMULASI KEBIJAKAN - Zuhri, Sholehudin; Delianoor, Nandang A.; Rahmatunnisa, Mudiyati (Al-Ijtima`i: International Journal of Government and Social Science, 2018)
The formation of electoral regulations is often synonymous with a dynamic political process, which is marked by the special attention of policy actors and institutions that have authority in policy formulation. The Presidential Threshold which is one of the crucial issues becomes an important instrument for factions in parliament in transforming its political preferences into Laws. By using qualitative methods, through the analysis of political attitudes and decisions fractions and analysis of meeting notesin discussion for theelection rule draft will be obtained a comprehensive picture of the political process of election regulation formulation. This study provides an idea that the power of parties with simple majority in the DPR in policy formulation can be seen from the correlation with the government and the distribution of power in government. With this power, the choice of policy on presidential threshold tends to be easier to get political support.